CHARACTERISTICS AND TREATMENT OUTCOMES OF HOSPITAL-ACQUIRED PNEUMONIA CAUSED BY ACINETOBACTER BAUMANNII IN THE RESPIRATORY DEPARTMENT OF THONG NHAT HOSPITAL - Ngân, Huỳnh Thị Thanh; Hoàng, Ngô Thế; Trí, Phạm Minh; Hồng, Phạm Thị Thu (Journal of Health and Aging, 2025)
This study aimed to characterize the clinical and paraclinical features, treatment outcomes, and antibiotic resistance patterns of Acinetobacter baumannii-associated hospital-acquired pneumonia (HAP) in elderly patients. A cross-sectional descriptive study was carried out on 75 hospitalized patients aged 60 years and above who were diagnosed with A. baumannii-related HAP. The study took place at the Department of Respiratory Medicine, Thong Nhat Hospital, from April 2024 to April 2025. The majority of patients exhibited clinical manifestations including fever, productive cough, dyspnea, auscultatory crackles, leukocytosis, elevated C-reactive protein (CRP) levels, and chest radiographs revealing infiltrates in over 70% of cases. Altered mental status was notably prevalent among elderly patients, affecting 65.3%. The most frequently utilized empirical antibiotic regimens were ceftazidime plus gentamicin, piperacillin/tazobactam plus levofloxacin, and ceftazidime pus ciprofloxacin; however, only 21.3% of these empirical therapies aligned with antibiotic susceptibility testing results. Multidrug-resistant A. baumannii accounted for 84% of isolates, with 21.3% classified as multidrug-resistant (MDR), 50.7% as extensively drug-resistant (XDR), and 13.3% as pandrug-resistant (PDR). Resistance rates to β-lactam/β-lactamase inhibitor combinations and cephalosporins exceeded 85%, resistance to quinolones and aminoglycosides ranged between 60–70%, and carbapenem resistance was approximately 50%. Colistin was identified as the sole antibiotic demonstrating efficacy exceeding 70%. The treatment failure rate was 65.3%, which was significantly associated with age, duration of hospitalization, and inappropriate empirical antibiotic therapy. The clinical and paraclinical characteristics of hospital-acquired pneumonia (HAP) caused by A. baumannii in elderly patients are distinctive, with altered mental status being a prominent feature. A. baumannii exhibited resistance to the majority of antibiotics tested, leaving colistin as the only relatively effective therapeutic option. Nonetheless, managing HAP caused by A. baumannii in the elderly remains a formidable challenge, reflected in a notably high mortality rate. Factors such as advanced age, prolonged hospitalization, and inappropriate empirical antibiotic use were significantly correlated with treatment failure